Objective measurement of sleep in mild cognitive impairment: A systematic review and meta-analysis. (August 2020) - D'Rozario, Angela L.; Chapman, Julia L.; Phillips, Craig L.; Palmer, Jake R.; Hoyos, Camilla M.; Mowszowski, Loren; Duffy, Shantel L.; Marshall, Nathaniel S.; Benca, Ruth; Mander, Bryce; Grunstein, Ronald R.; Naismith, Sharon L.
Summary: Older adults with mild cognitive impairment (MCI) are at-risk of developing dementia, particularly Alzheimer's disease. While some research suggests that alterations in sleep architecture may mediate cognitive decline, the nature and magnitude of changes to sleep macro- (sleep stages) and micro-architecture (electroencephalography (EEG) oscillations) in MCI is not yet clear. This study aimed to systematically review and meta-analyse case–control studies objectively measuring sleep in MCI. A systematic search was conducted using PubMed, Scopus, Web of Science, Embase and Psycinfo databases and after review, a total of 10 studies met inclusion criteria. Of these, all reported sleep macro-architecture and four reported micro-architecture outcomes. A combined total of 430 participants (209 with and 221 without MCI) underwent objective sleep assessments in the included full text articles. Findings show that compared to healthy controls, those with MCI have pronounced changes in sleep macro-architecture with greater wake after sleep onset, reduced total sleep time, lower sleep efficiency, longer sleep onset latency, longer rapid eye movement sleep (REM) latency, reduced REM sleep, greater N1 sleep, and worse severity of hypoxemia. Pooling of sleep micro-architecture EEG measures was not possible due to limited studies, however reduced spindles in non-REM sleep and greater EEG slowing in REM sleep were reported.